Define learning outcomes in terms of processes and contents: the cognitive operations - Roberto Trinchero (Formare, 2022)
How is it possible to define learning outcomes in school education? How can they be useful for rationalizing programming, teaching, learning and evaluation? The article describes the potential associated with a good definition of learning outcomes in terms of thought processes and learning contents, which define the cognitive operations that the learner must be able to implement in the facing of specific tasks. A model for defining learning outcomes that uses descriptors with explicit and shared formulation (R-I-Z-A model) is then presented. The model can be used both to operationalize skills and competences of the student.